2019
DOI: 10.1111/1475-6773.13227
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Medicare copayments for skilled nursing facilities on length of stay, outcomes, and costs

Abstract: Objective To investigate the impact of Medicare's skilled nursing facility (SNF) copayment policy, with a large increase in the daily copayment rate on the 20th day of a benefit period, on length of stay, patient outcomes, and costs. Data Sources and Study Setting Retrospective cohort study from 2012 to 2016 using Medicare claims and SNF assessment data, including SNF admissions for Medicare fee‐for‐service beneficiaries. Study Design We first estimate how changes in Medicare's SNF copayment on the 21st day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Race/ethnic disparities in SNF admissions may be explained by differences in access to and quality of care facilities, family structures, social networks, and caregiving. Studies showed that African American older adults are less likely to endorse assisted living facilities and SNF admissions31 and receive more assistance and support from their family 32,33. We found that non-Hispanic Whites evidenced a greater likelihood of receiving informal caregiving, whereas there was no difference in the amount of informal caregiving received.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Race/ethnic disparities in SNF admissions may be explained by differences in access to and quality of care facilities, family structures, social networks, and caregiving. Studies showed that African American older adults are less likely to endorse assisted living facilities and SNF admissions31 and receive more assistance and support from their family 32,33. We found that non-Hispanic Whites evidenced a greater likelihood of receiving informal caregiving, whereas there was no difference in the amount of informal caregiving received.…”
Section: Discussionmentioning
confidence: 50%
“…Studies showed that African American older adults are less likely to endorse assisted living facilities and SNF admissions 31 and receive more assistance and support from their family. 32,33 We found that non-Hispanic Whites evidenced a greater likelihood of receiving informal caregiving, whereas there was no difference in the amount of informal caregiving received. We identified race/ethnic disparities in SNF admission even after accounting for socioeconomic measures, as well as concurrent outcomes of informal caregiving hours received and hospitalizations.…”
Section: Sociodemographic Factorsmentioning
confidence: 68%
See 1 more Smart Citation
“…Another strand of the literature, on the effect of user fee (consisting of copayment and cost-sharing) changes on healthcare utilization, applied a difference-in-differences (DID) regression model to evaluate the effect of user fees on the utilization of various healthcare services. In general, a negative association between user fees and healthcare utilization was found for inpatient care services [13][14][15], outpatient care services [14,[16][17][18][19][20][21][22], long-term care utilization [23,24], psychiatric care services [25,26], rehabilitation care services [27] and prescription drug usage [28][29][30].…”
Section: Literature Reviewsmentioning
confidence: 99%
“…In addition to hospitals, local clinics in Taiwan are built to deal with primary care. Over 80% of children (age < 15) receive their outpatient care from the local clinics, and the elderly (aged 65 and older) and youth (aged [15][16][17][18][19][20][21][22][23][24] contribute the largest (approximately 36.88-38.90%) and smallest shares (approximately 3.03-3.83%) of total outpatient care visits, respectively, to medical centers, regional hospitals, and district hospitals [2,5]. It is important to note that the reimbursement payments per outpatient visit to district hospitals (NT$ 1770 or about USD 59), regional hospitals (NT$ 2445 or about USD 82) and medical centers (NT$ 3261 or about USD 109) were 2.37-4.36 times higher than those made to local clinics (NT$ 748 or about USD 25) in 2016 [2].…”
Section: Introductionmentioning
confidence: 99%